Pulmonary embolism at autopsy in cancer patients. (26th March 2021) - Gimbel, Inge A.; Mulder, Frits I.; Bosch, Floris T. M.; Freund, Jan Erik; Guman, Noori; van Es, Nick; Kamphuisen, Pieter W.; Büller, Harry R.; Middeldorp, Saskia
Abstract: Background: Pulmonary embolism (PE) is a potentially fatal disease, but data on the incidence of fatal PE in cancer patients are scant. Objective: We sought to estimate the proportion of cancer patients with PE at autopsy. Methods: For this retrospective cohort study, all autopsy reports of cancer patients were retrieved from PALGA: Dutch Pathology Registry and used for data extraction. The primary outcome was PE at time of autopsy, defined as any clot obstructing a pulmonary artery. The secondary outcome was venous thromboembolism, defined as the composite of thrombotic PE, deep vein thrombosis, splanchnic vein thrombosis, or internal jugular vein thrombosis. Results: A total of 9571 cancer patients were included. In 1191 (12.4%; 95% confidence interval [CI], 11.8‐13.1) patients, one or more PE events were observed at autopsy, of whom 1074 (90.2%) had a thrombotic embolism, 168 (14.1%) a tumor embolism, 9 (0.8%) a septic embolism, 7 (0.6%) a fat tissue embolism, and 3 (0.3%) a bone marrow embolism. Among patients with PE for whom the cause of death was specified in the autopsy report, death was considered PE‐related in 642 patients (66.7%), which was 6.7% of the total study population. Venous thromboembolism was observed in 1223 (12.8%; 95% CI, 12.1‐13.5) patients. Conclusion: The proportion of PE in cancer patients at autopsy is substantial. Although the study population is not representative for the total cancer population, it suggests that PE is an important disease complication in cancer patients.